The Nutrients Potential of Agricultural Waste as Feed of Ruminants in Southeast Sulawesi - Rahman, Rahman; Hafid, H.; Rahadi, S.; Aka, R.; Anas, A. A.; Baena, S. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The deelopets of uiats’ podutio hae to suppot  feed aailailit eithe i quantity or in quality. Problems of providing feeds in Southeast Sulawesi were limited land for foragecultivation and season fluctuation. Agricultural and plantation waste have great potential to use asalteatie uiat’s feed. This eseah as aied to aalze the utiets potetial ofagricultural waste in Southeast Sulawesi as ruminant feed. The data obtained can be used as areference for the formulation of ratios of uiats’ aiteae, podutio, ad epodutionutrition based on its genetic potential. The observed variables were water content, crude protein,crude fat, crude fiber, and total digestible nutrient (TDN). The results showed that the higher proteincontent were obtained from kapok seeds (27,71%), followed by tofu waste (21.73%), groundnutshell (19.53%). Meanwhile high crude fiber were obtain from groundnut shell, cacao pods, and ricestraw, respectively 35,63, 32.23 and 31.64%.Key words:  ruminant, agricultural waste, nutrients, crude protein, crude fat, and TDN